Does Crop Diversification Involve a Trade-Off Between Technical Efficiency and Income Stability for Rural Farmers? Evidence from Zambia - Agness Mzyece (Agronomy, 2020)
Crop diversification is a climate-smart agricultural technique which helps to improve resilience for farmers in the face of volatile weather due to climate change. Previous research on its effects on technical efficiency has shown mixed results. Despite burgeoning literature on the subject, an important research question that remains uninvestigated is: does crop diversification involve a compromise between technical efficiency and resilience (income stability) for rural farmers? Using nationally representative rural household survey data from Zambia, this study empirically answers this research question. We employ the Data Envelopment Approach (DEA) for efficiency and a two- step least-squares approach for income variability. Our results show evidence that crop diversification significantly improves income stability but significantly reduces technical efficiency. The paper provides useful implications for policies that promote crop diversification in Zambia and other countries.